FORMULASI KEBIJAKAN MASYARAKAT SADAR WISATA DALAM USAHA MENINGKATKAN KUNJUNGAN WISATA UNTUK PENINGKATAN PENDAPATAN ASLI DAERAH - Natalia Hartini Kristian; Hadiwiyono Hadiwiyono (JOURNAL AKSES STIA MALANG, 2020)
The tourism sector is currently a promising prima donna, for that with the authority possessed bythe region it can make local tourism potential as profitable economic and financial sources. In thedevelopment of tourism, elements involved in it are needed, namely the government itself, the privatesector and the local tourism-aware community. To realize regional independence in development and takecare of their own household, local governments must explore financial sources that exist in the region.One of them is exploring the potential of regional tourism because it is considered the most potentialfactor to contribute to PAD. In the Master Plan for Tourism Development of East Manggarai Regency for2015-2025, it aims to, among others, build regional tourism destinations with a cultural perspective,development of tourism infrastructure, tourism marketing efforts as an effort to foster interest in travelingthat is built in an integrated manner between the government, the business world and the community.From these efforts, finally regional income will get results in the form of increasing Regional OriginalIncome, and the East Manggarai area will be known outside the region and even allow it to be knownoutside the island and even outside the country of Indonesia.Keywords: Policy Formulation, Increasing Regional Original Income